2017
DOI: 10.1107/s2053230x17003508
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary neutron diffraction analysis of challenging human manganese superoxide dismutase crystals

Abstract: Superoxide dismutases (SODs) are enzymes that protect against oxidative stress by dismutation of superoxide into oxygen and hydrogen peroxide through cyclic reduction and oxidation of the active-site metal. The complete enzymatic mechanisms of SODs are unknown since data on the positions of hydrogen are limited. Here, methods are presented for large crystal growth and neutron data collection of human manganese SOD (MnSOD) using perdeuteration and the MaNDi beamline at Oak Ridge National Laboratory. The crystal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…NMR and X-ray crystallography are not very sensitive to revealing the positions of hydrogen, especially on solvent molecules. Recently, neutron diffraction experiments, which can reveal hydrogen positions, have been employed to investigate human MnSOD [ 84 ]. The experiments use a neutron diffractometer tailored to biological samples called the Macromolecular Neutron Diffractometer (MaNDi), which opened for academic use at Oak Ridge National Laboratory in 2014 [ 93 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…NMR and X-ray crystallography are not very sensitive to revealing the positions of hydrogen, especially on solvent molecules. Recently, neutron diffraction experiments, which can reveal hydrogen positions, have been employed to investigate human MnSOD [ 84 ]. The experiments use a neutron diffractometer tailored to biological samples called the Macromolecular Neutron Diffractometer (MaNDi), which opened for academic use at Oak Ridge National Laboratory in 2014 [ 93 ].…”
Section: Resultsmentioning
confidence: 99%
“…While protonation to a positive charge is unfavorable at the manganese-containing active site, the net sum of proton transfers is energetically favorable. Borgstahl and collaborators have recently employed the use of neutron diffraction to directly detect hydrogen positions and observed protonation of His30 ( Figure 4 ) [ 84 ]. This also suggests that WAT2 can be protonated as it is the nearest hydrogen-bond acceptor/donor to His30 in the crystal structure.…”
Section: Proton Transfers and The Hydrogen Bond Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, due to the superior pulse resolution of the DM, despite the minimal advantage in the overall counting statistics of the CM, we have concluded that the DM is the best choice for the new diffractometer at JSNS to target proteins with large unit cells over 250 Å [5,6]. Recently, data collection on MaNDi [7] installed at DM in Spallation Neutron Source (SNS) at Oak Ridge National Laboratory (ORNL) has been reported for a crystal with largest unit cell edge (240 Å) [8].…”
Section: Introductionmentioning
confidence: 99%
“…However, by using protein perdeuteration we can reduce the incoherent scattering by a factor of 40, enhancing the signal to noise ratio and enabling data collection from small crystals with large unit cell axes. The combination of perdeuteration with high resolution TOF crystallography has enabled data collection on one of the most challenging systems to be studied with neutrons to date [5][6][7][8] .…”
mentioning
confidence: 99%